Normatyvinis vyriškumas tarpukario Lietuvos spaudoje ir reklamoje: karininko įvaizdis - Bankauskaitė-Sereikienė, Gabija; Būblaitytė, Inga (Respectus Philologicus, 2017)
The present article is an extended research of the expression of normative masculinity, aiming at complementing the studies on the history of culture and advertising, and the perception of masculinity in the First Independent Republic of Lithuania as well as demonstrating the tendencies of male selfidentification process in the interwar context. First research results were published in the article “Masculinity Representation in Lithuanian Interwar Press Advertising” (Bankauskaitė, Stravinskaitė 2016). The prevailing images of masculinity were divided into several groups: a heroic superman, a successful careerist, a family man and a hedonistic or narcissistic man. This article complements the normative collection of masculinity with the image traits of an officer. It is the one who, due to the influence of aesthetic standards, fundamental national values active, physical education and aviation achievements, was associated with the highest level of masculinity in the interwar advertising. Active masculine physical power, courage, determination and a wish to dominate, conveyed in the advertisements and articles, are especially important constituent parts of a normative model of masculinity. The model of an officer includes the images of a young, handsome, and educated gentleman who served as a role model for every man in the interwar society.